High-yield production of graphene by liquid-phase exfoliation of graphite - GOUNKO, IOURI; NICOLOSI, VALERIA; GOODHUE, ROBBIE; SCARDACI, VITTORIO; COLEMAN, JONATHAN NESBIT; BOLAND, JOHN; DUESBERG, GEORG STEFAN (My University, 2008)
Graphene is at the centre of nanotechnology research. In order to fully exploit its outstanding properties, a mass production method is necessary. Two main routes are possible: large-scale growth or large-scale exfoliation. Here, we demonstrate graphene dispersions with concentrations up to ~0.01 mg/ml by dispersion and exfoliation of graphite in organic solvents such as N-methyl- pyrrolidone. This occurs because the energy required to exfoliate graphene is balanced by the solvent-graphene interaction for solvents whose surface energy matches that of graphene. We confirm the presence of individual graphene sheets with yields of up to 12% by mass, using absorption spectroscopy, transmission electron microscopy and electron diffraction. The absence of defects or oxides is confirmed by X-ray photoelectron, infra-red and Raman spectroscopies. We can produce conductive, semi-transparent films and conductive composites. Solution processing of graphene opens up a whole range of potential large-scale applications from device or sensor fabrication to liquid phase chemistry.
PUBLISHED
Keywords: WALLED CARBON NANOTUBES; SUSPENDED GRAPHENE